'Mind our mouths and beware our talk': Stylometric analysis of character dialogue in The Darjeeling Limited. (1st June 2019) - Buckland, Warren
Stylometry uses statistical reasoning to quantify the linguistic attributes of written texts. In this article I draw upon current developments in computer-based stylometric studies to quantify the language of screenplays. I take as my starting point John F. Burrows's seminal stylometric study of dialogue in Jane Austen's novels (Computation into Criticism [Burrows 1987]) to identify and quantify the linguistic habits of major screenplay characters, habits that constitute their distinctive voice. Analysis of the dialogue of the three Whitman brothers in The Darjeeling Limited (screenplay by Wes Anderson, Roman Coppola and Jason Schwartzman, dated 22 November 2006) will serve as a preliminary case study. I aim to use the work of Burrows as the starting point in establishing a new research programme within screenplay studies, one based on the stylometric analysis of the language of screenplays.